PELANGGARAN HAK ASASI MANUSIA PADA DEMONSTRAN KUDETA MYANMAR DITINJAU DARI PERSPEKTIF DEKLARASI UNIVERSAL HAK ASASI MANUSIA (DUHAM) - Daud Mahaldi Fernando Tampubolon; Retno Dewi Pulung Sari (UNES Law Review, 2022)
The Myanmar coup repeated itself in 2020 after it occurred in 1990 when Suu Kyi won the general election for the head of government from the NLD party. Triggered military unrest in Myanmar and carried out a leadership coup again, and arrested Suu Kyi for indications of fraud committed when the election will hold. The incident started a demonstration by the community against the Dimyanmar anti-coup was create chaos in the state of Myanmar. There have been many rejections made by the people of Myanmar towards the military intervention carried out at this time. As a result of this refusal, the military did inhuman things, such as arresting and shooting at demonstrators who demonstrated with the gimmick of security measures. They indicate the gross human rights violations that the military is currently confirming. After all, it has committed arbitrary actions against the protester and never underestimated. Hundreds of people get shot, and many are still unknown because they become hostages. On this basis, it is necessary to carry out a comprehensive study of the events that have occurred when there are victims who have fallen. Considering that legally the right to express an opinion is a fundamental right recognized by the ICCPR and DUHAM as the vanguard of the UN's seriousness in carrying out the mandate of recognizing human rights as a right. nature that is recognized and upheld.)